Beta 3 Adrenergic Receptor Activation Rescues Metabolic Dysfunction in Female Estrogen Receptor Alpha-Null Mice - Clookey, Stephanie L.; Welly, Rebecca J.; Shay, Dusti; Woodford, Makenzie L.; Fritsche, Kevin L.; Rector, R. Scott; Padilla, Jaume; Lubahn, Dennis B.; Vieira-Potter, Victoria J. (Frontiers in Physiology, 2019)
Metabolic disease risk escalates following menopause. The mechanism is not fully known, but likely involves reduced signaling through estrogen receptor alpha (ERα), which is highly expressed in brown and white adipose tissue (BAT and WAT). Objective: Test the hypothesis that uncoupling protein (UCP1) activation mitigates metabolic dysfunction caused by loss of signaling through ERα. Methods: At 8 weeks of age, female ERα knock out (KO) and wild-type mice were housed at 28°C and fed a Western-style high-fat, high sucrose diet (HFD) or a normal low-fat chow diet (NC) for 10 weeks. During the final 2 weeks, they received daily injections of CL 316,256 (CL), a selective β3 adrenergic agonist, or vehicle control (CTRL), creating eight groups: WT-CTRL, WT-CL, KO-CTRL, and KO-CL on HFD or NC; n = 4–10/group. Results: ERαKO demonstrated exacerbated HFD-induced adiposity gain (P < 0.001) and insulin resistance (P = 0.006). CL treatment improved insulin sensitivity (P < 0.05) and normalized ERαKO-induced adiposity increase (P < 0.05). In both genotypes, CL increased resting energy expenditure (P < 0.05) and induced WAT beiging indicated by increased UCP1 protein in both perigonadal (PGAT) and subcutaneous (SQAT) depots. These effects were attenuated under HFD conditions (P < 0.05). In KO, CL reduced HFD energy consumption compared to CTRL (P < 0.05). Remarkably, CL increased WAT ERβ protein levels of both WT and KO (P < 0.001), revealing CL-mediated changes in estrogen signaling may have protective metabolic effects. Conclusion: CL completely restored metabolic dysfunction in ERαKO mice. Thus, UCP1 may be a therapeutic target for treating metabolic dysfunction following loss of estrogen receptor signaling.